Genetic Diversity of plasmodium knowlesi red cell invasion genes (pknbpxa and pknbpxb) and their association with parasitaemia - Mohammed Atique, Ahmed (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Human infections with Plasmodium knowlesi, a parasite of long-talied (Macaca fascicularis) and pig-tailed macaques (Macaca nemestrina), continue to be reported in most countries within Southeast Asia and majority of the humans cases occur in Malaysian Borneo. The parasite has a 24 hour erythrocytic cycle and parasitaemia has been shown to be associated with the development of severe malaria in humans. The parasite invades host red blood cells via specific receptors on these cells using multiple parasite invasion ligands and the reticulocyte binding-like (RBL) proteins are one such family of ligands There are two RBL proteins in P. knowlesi; normocyte binding protein xa and xb (Pknbpxa and Pknbpxb) which are expressed at merozoite apex during invasion process. The polymorph isms at these RBL genes may be critical to the increase in peripheral parasitaemia in humans, thereby giving an invasion advantage to the parasite. Therefore, this study was designed to test the hypothesis that parasitaemia is associated with particular aJleIes or haplotypes of Pknbpxa and Pknbpxb genes from clinically well characterised patient isolates recruited from two study sites; Sibu and Sarikei divisions of Sarawak. Genetic diversity and signatures of natural selection acting on these loci from patient isolates were also determined. In the first instance, coding regions with highest diversity within Pknbpxa (8.5 kb) and Pknbpxb (3.1 kb) fragments from five P. knowlesi reference isolates recruited from geographically distinct regions of Sarawak were identified through high stringency amplification, cloning and sequencing methods. Sequence analyses of Pknbpxa and Pknbpxb from five P. knowlesi reference isolates revealed that the overall nucleotide diversity of Pknbpxa gene was high (n = 0.01429). Lower diversity was observed for Pknbpxb gene (n = 0.00381). Regions of highest diversity were localised towards the 5' erythrocyte binding region of Pknbpxa gene (nucleotide position 389 to 1388, n = 0.0241). Highest diversity within the Pknbpxb reference sequences were observed from nucleotide position 2157 to 3156 (n = 0.00582). Based on these highly polymorphic regions, haplotypes were identified by sequencing (Pknbpxa 885 bp and Pknbpxb 897 bp) fragment from each gene which identified 75 Pknbpxa haplotypes with high haplotype diversity (Hd = 0.9729) and 51 Pknbpxb haplotypes with haplotype diversity (Hd = 0.922) from 138 and 134 P. knowles; patient isolates respectively. Phylogenetic analyses of Pknbpxa fragments from the five P. knowles; reference isolates as well as the haplotyping fragments from 138 patient isolates revealed that the gene was dimorphic (KH195 group; n = 77 and KH273 group; n = 61). Deduced amino acid sequences obtained from the five reference isolates for both genes showed that all cysteine residues were conserved thus indicating intact binding function to host erythrocyte. Similar conservation of cysteine residues were observed for all the 138 sequences obtained from the Pknbpxa haplotyping region. Analyses of natural selection using various tests revealed that the Pknbpxa gene is under strong positive selection while the Pknbpxb gene might be under negative selection within the parasite population. Natural selection with isolates within each dimorphic groups of Pknbpxa gene revealed that there might be an ongoing selective sweep towards KH273 group due to strong positive selection. Genetic association analyses of non-synonymous SNPs of Pknbpxa and Pknbpxb with parasitaemia showed that there were significant associations between two Pknbpxa SNPs C913T (minor allele 'C' representing 18.8% of isolates) (r = 0.2100, P =0.0149), G 1l02C (minor allele 'G' representing in 30.4% of isolates) (r = 0.171, P = 0.047) and one Pknbpxb SNP A3115G (major allele 'G' representing in 59% of isolates) (r = 0.1809, P = 0.0394). These results suggest that different variants of Pknbpxa and Pknbpxb are involved in increasing erythrocyte invasion efficiency resulting in increased parasitaemia in patients. Further studies are necessary to detennine whether more SNPs of these genes associate with patient parasitaemia